2020
DOI: 10.1088/1757-899x/737/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

State of Building Information Modelling (BIM) adoption in Iraq

Abstract: Building Information Modelling (BIM) is one of the most promising technologies in the Architecture, Engineering and Construction (AEC) industry. However, while a number of studies have shown the benefits of BIM, especially in infrastructure projects, barriers exist to actualising these benefits through implementation. In Iraq, there is a lack of BIM adoption among construction firms because industry practitioners are not interested in BIM and the firms do not have the adequate experience in this technology. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…R1 [ 17 ], R2 [ 18 ], R3 [ 19 ], R4 [ 10 ], R5 [ 20 ], R6 [ 21 ], R7 [ 22 ], R8 [ 23 ], R9 [ 24 ], R10 [ 25 ], R11 [ 26 ], R12 [ 13 ], R13 [ 27 ], R14 [ 28 ], R15 [ 29 ], R16 [ 30 ], R17 [ 31 ], R18 [ 32 ], R19 [ 26 ], R20 [ 33 ], R21 [ 34 ], R22 [ 35 ], R23 [ 36 ], R24 [ 37 ], R25 [ 38 ], R26 [ 39 ], R27 [ 40 ], R28 [ 41 ], R29 [ 42 ], R30 [ 43 ], R31 [ 44 ], R32 [ 45 ], R33 [ 46 ], R34 [ 47 ], R35 [ 48 ], R36 [ 49 ], R37 [ 50 ], R38 [ 51 ], R39 [ 52 ], R40 [ 53 ], R41 [ 54 ], R42 [ 55 ], R43 [ 56 ], R44 [ 57 ], 45 [ 58 ], 46 [ 59 ], R47 [ 60 ], R48 [ 61 ], R49 [ 62 ], R50 [ 63 ], R51 [ 64 ], R52 [ 65 ], R53 [ 66 ], R54 [ 67 ], R55 [ 68 ], R56 [ 69 ], R57 [ 70 ], R58 [ 71 ], R59 [ 72 ], R60 [ 73 ], R61 [ 74 ], R62 [ 75 ], R63 [ 76 ], R64 [ 77 ], R65 [ 78 ], R66 [ 79 ], R67 [ ...…”
Section: Resultsmentioning
confidence: 99%
“…R1 [ 17 ], R2 [ 18 ], R3 [ 19 ], R4 [ 10 ], R5 [ 20 ], R6 [ 21 ], R7 [ 22 ], R8 [ 23 ], R9 [ 24 ], R10 [ 25 ], R11 [ 26 ], R12 [ 13 ], R13 [ 27 ], R14 [ 28 ], R15 [ 29 ], R16 [ 30 ], R17 [ 31 ], R18 [ 32 ], R19 [ 26 ], R20 [ 33 ], R21 [ 34 ], R22 [ 35 ], R23 [ 36 ], R24 [ 37 ], R25 [ 38 ], R26 [ 39 ], R27 [ 40 ], R28 [ 41 ], R29 [ 42 ], R30 [ 43 ], R31 [ 44 ], R32 [ 45 ], R33 [ 46 ], R34 [ 47 ], R35 [ 48 ], R36 [ 49 ], R37 [ 50 ], R38 [ 51 ], R39 [ 52 ], R40 [ 53 ], R41 [ 54 ], R42 [ 55 ], R43 [ 56 ], R44 [ 57 ], 45 [ 58 ], 46 [ 59 ], R47 [ 60 ], R48 [ 61 ], R49 [ 62 ], R50 [ 63 ], R51 [ 64 ], R52 [ 65 ], R53 [ 66 ], R54 [ 67 ], R55 [ 68 ], R56 [ 69 ], R57 [ 70 ], R58 [ 71 ], R59 [ 72 ], R60 [ 73 ], R61 [ 74 ], R62 [ 75 ], R63 [ 76 ], R64 [ 77 ], R65 [ 78 ], R66 [ 79 ], R67 [ ...…”
Section: Resultsmentioning
confidence: 99%
“…E-Through their research, Alsaeedi et al [11] have identified obstacles to achieving the anticipated benefits of using BIM in projects, including the fact that industrial practitioners are not engaged in BIM applications and have insufficient BIM expertise with businesses. The researcher concludes that the phenomenon of reluctance and not accepting change from the beginning is one of the most significant reasons for not applying BIM widely, especially given the presence of a small number of those who apply BIM, their experience ranging from 3-to-6 years only.…”
Section: Bim In Iraqi Projectsmentioning
confidence: 99%
“…BIM is a highly advanced technology in the Architecture, Engineering, and Construction (AEC) industry [18]. The researchers employed an integrated BIM game engine solution to enhance visualisation and teaching within the construction sector [19,20].…”
Section: Introductionmentioning
confidence: 99%